Determining the Roles of the Anterior Cruciate Ligament, Posterolateral Corner, and Medial Collateral Ligament in Knee Hyperextension Using the Heel-Height Test. Issue 4 (8th April 2022) - Perry, Allison K.; Knapik, Derrick M.; Gursoy, Safa; Alter, Thomas D.; Clapp, Ian M.; Verma, Nikhil N.; LaPrade, Robert F.; Chahla, Jorge
Background: Anterior cruciate ligament (ACL) tears are often associated with other ligamentous injuries. The side-to-side difference in heel height can represent a valuable diagnostic tool in the setting of multiligamentous injuries. Purpose: To assess in a cadaveric model how sequential sectioning of the static stabilizing structures of the knee (ACL, fibular collateral ligament [FCL], popliteus tendon [PLT], popliteofibular ligament [PFL], and medial collateral ligament [MCL]) influences heel-height measurements when comparing groups undergoing initial transection of the ACL versus FCL and to assess posterior tibial slope after sequential sectioning. Study Design: Controlled laboratory study. Methods: A total of 16 fresh cadaveric knees were carefully dissected to expose the ACL, FCL, PLT, PFL, and MCL. Each knee was randomized to either the ACL-first or FCL-first group based on the initial structure sectioned. The sectioning order was as follows: (1) ACL or FCL, (2) FCL or ACL, (3) PLT, (4) PFL, and (5) MCL. Heel height was measured with a standardized superiorly directed 12-N·m force applied to the knee while stabilizing the femur; heel height was also measured with a clinician-applied force. The measurements were compared between and within groups for each sectioned state. The correlation between tibial slope and heel-height measurements was analyzed. Results: There were no significant differences in heel-height measurements between the ACL-first and FCL-first groups ( P = .863). Combined ACL-FCL injuries led to a 2.85 ± 0.83–cm increase in heel height compared to the intact state. Significant increases in heel height occurred after all sectioned states, except the PFL sectioned state. Combined ACL–posterolateral corner (PLC) injuries resulted in a 3.72 ± 1.02–cm increase in heel height, and additional sectioning of the MCL resulted in a 4.73 ± 1.35–cm increase compared to the intact state. Tibial slope was not correlated with increases in heel height after each sectioning ( P = .154). Conclusion: Combined ACL-FCL, ACL-PLC, and ACL-PLC-MCL injuries resulted in increasing mean heel-height measurements (2.85, 3.72, and 4.73 cm, respectively) compared to the intact state. Tibial slope was not found to influence increases in heel height. Clinical Relevance: The side-to-side difference in heel height may be a clinically relevant examination tool for diagnosing multiligament knee injuries.